A Study of Students’ Attitudes Towards The Use of Code Mixing in English Classroom - Setiawan, Wawan; Mandela, Fitra (Jurnal Bahasa Asing, 2023)
This present study aimed to explore students’ attitudes towards code mixing in English classroom through questionnaires and semi-structured interviews. There were 30 students involved and 5 of the students were chosen to be the interviewees. The results from the two instruments showed that the teacher frequently used English with Indonesian in English classroom, but they had a positive attitude. In contrast, the majority of the students were not happy when their teacher used full English in the classroom. They believed that code mixing was a practical solution and strategy applied by the teacher to make them learn English more easily.